(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Student-oriented approach in education has received a comprehensive description in numerous works of Russian and foreign researchers and continues to evolve rapidly. The implementation of student-oriented approach, the information and methodological support of students throughout the training period are the most effective when used of electronic information-educational environment of high school. The purpose of this article is to analyze the possibilities of using electronic information-educational university environment of university for the formation of an e-portfolio of achievements. The following methods were used during the research: analysis of the scientific literature on the issue of research, experimental teaching, questioning. Long-term researches in the field of quality and competence-oriented approach to education, which are conducted by the authors, allowed to develop and test two approaches to the formation of a student’s e-portfolio: by learning outcomes or by type of activity. This paper will present the structure of student’s e-portfolio, a brief description of its elements, as well as experience of creating e-portfolios by students of the Pskov State University. We share the view that the e-portfolio is an expression of qualitative and multi-level assessment of competencies, measuring individual progress of students, self-presentation for employers. The formation of an e-portfolio contributes to the implementation of student-oriented approach, it’s an important element of the competence-oriented approach to education. Electronic information-educational university environment of university allows to realize all this.